2019
DOI: 10.1016/j.joco.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular movement disorders following scleral buckling surgery: A case series study

Abstract: Purpose To evaluate ocular movement disorders after scleral buckling surgery (SBS) for retinal detachment. Methods In this prospective, observational, case series, 206 patients (206 eyes) with rhegmatogenous retinal detachment who underwent SBS and investigated at the strabismus ward of Farabi Eye Hospital in Iran between November 2011 and November 2014 were assessed. Patients were followed from 6 to 36 months after SBS to evaluate for strabismus. Logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
0
1
1
Order By: Relevance
“…[3] Previous studies have found an incidence of postoperative strabismus following retinal detachment surgery to range from 5% to 25%. [4,8,9] This is much higher than seen in our series, in which <1% of patients developed postoperative strabismus. Perhaps, our study did not capture patients with minor strabismic deviations and only captured those patients with symptomatic strabismus with significant prismatic deviations.…”
Section: Discussioncontrasting
confidence: 57%
“…[3] Previous studies have found an incidence of postoperative strabismus following retinal detachment surgery to range from 5% to 25%. [4,8,9] This is much higher than seen in our series, in which <1% of patients developed postoperative strabismus. Perhaps, our study did not capture patients with minor strabismic deviations and only captured those patients with symptomatic strabismus with significant prismatic deviations.…”
Section: Discussioncontrasting
confidence: 57%
“…Sampai saat ini belum terdapat rekomendasi terhadap penanganan yang tepat pada pasien strabismus pasca pemasangan scleral buckle. 5 Penulis melaporkan kasus esotropia pasca pemasangan buckle pada pasien laki-laki 31 tahun dengan gejala awal mata kanan kabur dan bergulir ke dalam paska dilakukan operasi pemasangan sclera buckle akibat ablasio retina. Laporan kasus ini dibuat bertujuan untuk menambah wawasan pengetahuan dalam menegakkan diagnosis, melakukan pemeriksaan, dan pertimbangan tatalaksana pada kasus esotropia pada pasien pasca operasi sclera buckle agar dapat memberikan terapi yang tepat pada pasien tersebut.…”
Section: Pendahuluanunclassified